2009
DOI: 10.1111/j.1475-6773.2009.00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Practice Location Choice by New Physicians: The Importance of Malpractice Premiums, Damage Caps, and Health Professional Shortage Area Designation

Abstract: Objective. To understand the factors affecting the choice of initial practice location by new physicians. Data Sources/Study Setting. A unique survey of exiting medical residents in New York State from 1998 to 2003. Study Design. We estimate conditional logit models to examine the factors affecting the choice of initial practice location by new physicians. Data Collection/Extraction Methods. We identify all physicians completing their training in obstetrics/gynecology or surgery and primary care physicians (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…47,53 Burden of educational debt was a direct and indirect factor in the choice to practice in an underserved area. 19,20,55 In a study of exiting residents in New York, primary care physicians were more likely to locate in an HPSA if their absolute undergraduate medical education debt was less than $100,000. 19 The study also suggested that primary care physicians with no debt were three times more likely than primary care physicians with any debt to locate in a shortage area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…47,53 Burden of educational debt was a direct and indirect factor in the choice to practice in an underserved area. 19,20,55 In a study of exiting residents in New York, primary care physicians were more likely to locate in an HPSA if their absolute undergraduate medical education debt was less than $100,000. 19 The study also suggested that primary care physicians with no debt were three times more likely than primary care physicians with any debt to locate in a shortage area.…”
Section: Resultsmentioning
confidence: 99%
“…49 While having no burden of debt may make the choice of locating in HPSAs more likely among primary care physicians, relieving debt burden would not necessarily improve chances of underserved practice among all specialties (e.g., surgery and obstetrics/gynecology). 19 Interestingly, the loan repayment programs demonstrate a high physician retention rate in underserved areas compared to other incentivized service-obligation programs. 52 More research focusing on new and current financial factors specific to health care and reimbursement reform is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond factors examined in this study, regional differences in the organization of healthcare delivery or the health insurance market may contribute to this pitcture. Lastly, similarities between neighboring states described above may be a reflection of similarities in medical training, which does not only affect medical decision making, forming a culture of medical reasoning and decision-making, but also practice locations, as the majority of physicians choose practices in relatively close proximity to the location of their residency 5,6…”
Section: Discussionmentioning
confidence: 99%
“…The data is consistent with studies finding that statutory limits on noneconomic damages have a positive effect on where physicians locate their practices. 32 Figure 3 also refutes any theory that fewer physicians practicing in Mississippi in recent years resulted in fewer medical accidents and thus fewer lawsuits. More physicians practicing in the state presumably would be associated with more lawsuits in the absence of tort reform, not fewer.…”
mentioning
confidence: 63%